Hybridization of Co3S4 and Graphitic Carbon Nitride Nanosheets for High-performance Nonenzymatic Sensing of H2O2 - Asha Ramesh; Ajay Ajith; Neeraja Sinha Gudipati; Siva Rama Krishna Vanjari; S. Abraham John; Vasudevanpillai Biju; Ch Subrahmanyam (Biosensors, 2023)
The development of efficient H2O2 sensors is crucial because of their multiple functions inside and outside the biological system and the adverse effects that a higher concentration can cause. This work reports a highly sensitive and selective non-enzymatic electrochemical H2O2 sensor achieved through the hybridization of Co3S4 and graphitic carbon nitride nanosheets (GCNNS). The Co3S4 is synthesized via a hydrothermal method, and the bulk g-C3N4 (b-GCN) is prepared by the thermal polycondensation of melamine. The as-prepared b-GCN is exfoliated into nanosheets using solvent exfoliation, and the composite with Co3S4 is formed during nanosheet formation. Compared to the performances of pure components, the hybrid structure demonstrates excellent electroreduction towards H2O2. We investigate the H2O2-sensing performance of the composite by cyclic voltammetry, differential pulse voltammetry, and amperometry. As an amperometric sensor, the Co3S4/GCNNS exhibits high sensitivity over a broad linear range from 10 nM to 1.5 mM H2O2 with a high detection limit of 70 nM and fast response of 3 s. The excellent electrocatalytic properties of the composite strengthen its potential application as a sensor to monitor H2O2 in real samples. The remarkable enhancement of the electrocatalytic activity of the composite for H2O2 reduction is attributed to the synergistic effect between Co3S4 and GCNNS.